The Implementation of Multimodal Approach to Teaching English Online in The Covid – 19 - Ika Purnama Sari; Rizky Khairunnisa Sormin; Anita Purba; Setiawati; Epi Supriyani Siregar (English Lecturers and Teachers Association (ELTA), 2023)
The advent of COVID-19 and the subsequent national lockdown has catapulted higher education institutions into emergency remote teaching. It is make the students must study from home. Multimodality is an emergent phenomenon that may influence how digital learning is designed. By the Multimodal the teacher and the students can study well, eventhough they are at home. Multimodal employed in highly interactive and immersive learning environments. In this research, the author investigates and analyzes the multimodal theory and proposes an effective way to teach English in higher education under the multimodal vision. This study aims to analyze the multimodal approach theory and proposes an effective way to teach English in higher education under the multimodal vision. The instrument used by the writer in this research is a questioner and interview. The interview was made after administering the questionnaires to verify the students’ responses. The questioner is sent by G-form. From the data and analysis that have been completed from the results of the questionnaire regarding the students’ interest in learning English. There are 47 respondents. The respondents or 93.7 % were attracted to learn English by Multimodal Approach. It means that the Multimodal Approach help to improve the quality of English language teaching in higher education institutions. The students can understand through a multimodal approach to teaching English Online in Higher Education during the covid-19. Keywords: Multimodal Approach, Online Learning, Teaching and Learning